2021
DOI: 10.3390/app11031088
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Production System Pondering upon Corporate Social Responsibility in Food Supply Chain: A Case Study

Abstract: Corporate social responsibility (CSR) has witnessed remarkable attention in academic studies as well as being widely conducted in different industries globally. This specific case was chosen as one of the biggest dairy companies that may be represented for Vietnam dairy supply chain management. This research aims to integrate CSR initiatives into food supply chain management to clarify the optimal replenishment policy, paying close attention to the relationship between midstream manufacturers and final custome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The study shows the close relationship between the company and consumers, which is reflected in its financial performance [13].…”
mentioning
confidence: 83%
“…The study shows the close relationship between the company and consumers, which is reflected in its financial performance [13].…”
mentioning
confidence: 83%
“…Corporate social responsibility (CSR) reflects a corporation's responsibility to society and a wider range of stakeholders other than its shareholders [1], which has drawn tremendous attention from researchers and managers due to its impact on corporate development. CSR has been found to be able to improve corporate performance [2][3][4][5], enhance corporate reputation [6][7][8], promote corporate innovation [9,10], reduce corporate risks [11,12], and maintain corporate stability in the face of emergencies to achieve economic recovery [13]. However, Wright and Ferris [14] found that CSR could damage enterprise value.…”
Section: Introductionmentioning
confidence: 99%